2018
DOI: 10.4236/ojbm.2018.63058
|View full text |Cite
|
Sign up to set email alerts
|

Tax Burden Implication of Tax Reform

Abstract: This study examines the effect of the 2007 reform pertaining to the corporate tax system on the tax burden of listed firms in Nigeria using the t-test and canonical correlation analysis. Data were collected from the financial statements of the 86 sampled firms for the period 2003-2011 subdivided into pre-reform (2003)(2004)(2005)(2006) and post reform (2008-2011) sub-periods for the purpose of comparing periods' tax burdens. Data were also segregated along the Nigerian Stock Exchange industrial sector classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Many other scholars have been actively promoting corporate tax cuts, but they have different opinions on the ways and effects of tax cuts. For example, Grubert and Altshuler [16] considered that changing the corporate income tax to personal income tax can significantly reduce the corporate tax rate; Hines Jr [17] considered that although the corporate tax rate in the United States provides a large number of additional deductions, tax exemptions, and tax credits, however, it creates the heaviest tax burden; Salaudeen and Atoyebi [18] demonstrated that the effect of tax reform was heterogeneous, which led to an increase or decrease in tax burdens in different industries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many other scholars have been actively promoting corporate tax cuts, but they have different opinions on the ways and effects of tax cuts. For example, Grubert and Altshuler [16] considered that changing the corporate income tax to personal income tax can significantly reduce the corporate tax rate; Hines Jr [17] considered that although the corporate tax rate in the United States provides a large number of additional deductions, tax exemptions, and tax credits, however, it creates the heaviest tax burden; Salaudeen and Atoyebi [18] demonstrated that the effect of tax reform was heterogeneous, which led to an increase or decrease in tax burdens in different industries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The sectoral analysis of diversification of the tax burden is carried out as a component of the analysis of tax systems and tax reforms (Jacobs and Spengel 1999;Nicodeme 2001;The World Bank Group 2006;Sybiryanka and Pyslytsya 2016;Carreras et al 2017;Boiko and Sytnyk 2018;Salaudeen and Atoyebi 2018;Boiko et al 2019;Bhattarai et al 2019). In Vietnam, the corporation income tax rate is highest in refined petroleum products (41.93%), followed by the agriculture sector (18.46%), health and social work (14.59%), and hotels and restaurants (12.32%) (Bhattarai et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Minton, Schrand and Walther, McGuire, Neuman, Omer et al measure the sustainability of a firm's tax strategy using the coefficient of variation for annual cash effective tax rates (ETRs or Cash ETR) (Nicodeme 2001;Minton et al 2002;McGuire et al 2013;Ma 2018;Ma and Park 2021). Many modern scientists support the idea of calculation of the cash effective tax rate for the needs of tax analysis (Dyreng et al 2008;Hanlon and Heitzman 2010;Tax Policy Briefing Book 2010;Hasan et al 2014;Edwards et al 2016;Bonsall et al 2017;Guenther et al 2017;Carreras et al 2017;Salaudeen and Atoyebi 2018;Dyreng et al 2019;Fernández-Rodríguez et al 2019;Hutchens et al 2020;Dhawan et al 2020;Nurwati and Kalbuana 2021). Shin and Park define two relative indicators in their research: the cash effective tax rate and the effective tax rate (Shin and Park 2022).…”
Section: Tax Sustainability Of the Companymentioning
confidence: 99%
“…However, whether proportional or progressive, the monetary measurement aspect remains common in the sense that the cognitive effort employed by subjects in the process of earning the income is not recognized, leading to different perceptions of progressive taxation (Tjondro et al, 2019). Most tax reforms conducted to redistribute tax burden results in the some sectors bearing more burden as others bear less burden after reforms (Salaudeen & Atoyebi, 2018). Yet, the consideration in redistribution has a basis other than the cognitive pressure in financial decision making of economic agents.…”
Section: Introductionmentioning
confidence: 99%